Analysis of Flavonoid and Antimicrobial Activity of Extracts of Hypericum perforatum - Naeem, Ismat; Saddiqe, Zeb; Patel, Asmita; Hellio, Claire (Asian Journal of Chemistry, 2010)
Ethyl acetate, n-butanol and methanol extracts of Hypericum perforatum were analyzed qualitatively and quantitatively for their flavonoid content by RP-HPLC. The components were detected by comparison with authentic standards of five flavonols (quercetin, myricetin, isorhamnetin, rhamnetin and kaempferol) and a flavone (luteolin). Quercetin and myricetin were present in all the three fractions while kaempferol was present only in n-butanol fraction. Isorhamnetin, rhamnetin and luteolin were not detected in the extracts. The total sum of detected flavonoids was highest in n-butanol fraction (8031.25 mg/kg fresh wt.) followed by ethyl acetate (4805.13 mg/kg fresh wt.) and methanol (4720.00 mg/kg fresh wt.). The extracts were also evaluated for their antibacterial activity against Bacillus subtilis, Pseudomonas aeruginosa, Sarcina lutae and Escherichia coli. The total extracts were tested at concentrations of 1, 10, 25 and 50 μg/μL. In vitro antibacterial studies were carried out in 96-well microplates. The nhexane and dichloromethane extracts were inactive against all the tested organisms at all experimental concentrations. The n-butanol and ethyl acetate extracts showed activity against all the tested bacterial strains at concentrations of 25 and 50 μg/μL while the methanolic extract was only active against B. subtilus at concentrations 25 and 50 μg/μL.